Chirac’s Gaullism – Why France Has Become the Driving Force behind the Effort to Build an Autonomous European Defence? - Marcel H. Van Herpen (Romanian Journal of European Affairs, 2004)
The author analyses Chirac’s European defence policy and how it fits into the Gaullist tradition. He starts by sketching the original Gaullism of General De Gaulle which is based on four pillars: a national industrial policy, an independent foreign policy, the possession of a French nuclear deterrent and the ambition to build an independent European defence. His efforts in the last realm, however, are blocked by the US and its European NATO allies. In the Non-Gaullist Interregnum between 1974-1995 President Giscard d’Estaing jeopardised the Gaullist legacy, but President François Mitterrand became – against all expectations – a ‘Socialist Gaullist’ and it was he who realised one of De Gaulle’s objectives by creating the Eurocorps. His successor, Jacques Chirac has conducted a highly volatile European policy. The author distinguishes no less than six different and often contradictory phases in Chirac’s European defence policy. Despite the failures, some successes, however, have been booked, especially after the Saint-Malo Summit with Tony Blair. But much will depend in the coming years on how Chirac will succeed his balancing act between the EU-25, the French-German tandem and the ‘Big Three’.